How effective are family-based and institutional nutrition interventions in improving children's diet and health? A systematic review - Andrew P. Black; Katina D'Onise; Robyn McDermott; Hassan Vally; Kerin O'Dea (BMC, 2017)
Abstract Background Effective strategies to improve dietary intake in young children are a priority to reduce the high prevalence of chronic non-communicable diseases in adulthood. This study aimed to assess the impact of family-based and school/preschool nutrition programs on the health of children aged 12 or younger, including the sustainability of these impacts and the relevance to socio-economic inequalities. Methods A systematic review of literature published from 1980 to December 2014 was undertaken. Randomised controlled trials involving families with children aged up to 12 years in high income countries were included. The primary outcomes were dietary intake and health status. Results were presented in a narrative synthesis due to the heterogeneity of the interventions and outcomes. Results The systematic search and assessment identified 39 eligible studies. 82% of these studies were set in school/preschools. Only one school study assessed the impact of involving parents systematically. The family-based programs which provided simple positive dietary advice to parents and regular follow-up reduced fat intake significantly. School and family-based studies, if designed and implemented well, increased F&V intake, particularly fruit. Effective school-based programs have incorporated role-models including peers, teachers and heroic figures, rewards and increased access to healthy foods. School nutrition programs in disadvantaged communities were as effective as programs in other communities. Conclusions Family and school nutrition programs can improve dietary intake, however evidence of the long-term sustainability of these impacts is limited. The modest overall impact of even these successful programs suggest complementary nutrition interventions are needed to build a supportive environment for healthy eating generally.